Grass - Gendry-Kim, Keum Suk (Drawn & Quarterly, 2019)
"Grass is a powerful anti-war graphic novel, offering up firsthand the life story of a Korean girl named Okseon Lee who was forced into sexual slavery for the Japanese Imperial Army during the second World War - a disputed chapter in 20th century Asian history. Beginning in Lee's childhood, Grass shows the leadup to World War II from a child's vulnerable perspective, detailing how one person experienced the Japanese occupation and the widespread suffering it entailed for ordinary Korean folk. Keum Suk Gendry-Kim emphasizes Lee's strength in overcoming the many forms of adversity she experienced. Grass is painted in a black ink that flows with lavish details of the beautiful fields and farmland of Korea and uses heavy brushwork on the somber interiors of Lee's memories."--